PENTINGKAH FASILITAS LAKTASI DI INSTITUSI PENDIDIKAN? - Setyani, Rizka Ayu (Jurnal Ilmiah Bidan (JIB), 2021)
The obligation to provide adequate lactation facilities in public areas, especially the working institutions have been governed by government regulations. However, not all institutions have decent lactation facilities, including college in Yogyakarta, whose majority of workers are women of productive age. The purpose of this research is to know the importance of lactation facilities in educational institutions based on the experience of nursing mothers and policy managers and policymakers in Yogyakarta College. Types of qualitative research with draft case studies. Sampling purposive (Snowball sampling) with the informant that has been or is breastfeeding and the key informant is Vice Rector II, head of HR Bureau, head of General Bureau and Finance. Analyze data with Miles and Hubberman content analysis. After a thorough interview of 10 informers of nursing workers, most say uncomfortable while breastfeeding in the workplace due to the absence of a special space for breastfeeding and privacy. The lactation room is considered important because it is the need for working mothers in the workplace. The procurement of lactation facilities has not been carried out because there have been no initiators and has not been a priority program at the leadership meeting. In conclusion, based on the needs analysis, it will be considered procurement of lactation facilities in education institutions.